2022
DOI: 10.1097/j.pain.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Estimating individualized treatment effects using a risk-modeling approach: an application to epidural steroid injections for lumbar spinal stenosis

Abstract: Supplemental Digital Content is Available in the Text.A “risk-modeling” approach was used in randomized controlled trials of back pain to examine heterogeneity of treatment effect guided by the Predictive Approaches to Treatment effect Heterogeneity Statement framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Another potential limitation of the study is that the findings with regards to feasibility and effectiveness may not generalize to settings outside the VA health care system, as patients in VA settings generally have higher levels of disability and psychological comorbidity than in civilian health care. [21] We have recently shown that procedural treatment effects on disability outcomes in CLBP can be larger in subgroups of people with higher predicted levels of disability, [23] leaving open the possibility that treatment effects in non-VA settings may be smaller than those in the current study. A specific limitation related to activity tracker-evaluated step counts was that post-MBB improvements in step counts were noted for many participants as compared to their pre-MBB steps, and these improvements had not returned to pre-MBB levels for some participants prior to randomization (even though pain intensity levels had returned to an intensity sufficient to warrant LRFA and were ≥4 on the NRS scale on the day of randomization).…”
Section: Discussionmentioning
confidence: 69%
“…Another potential limitation of the study is that the findings with regards to feasibility and effectiveness may not generalize to settings outside the VA health care system, as patients in VA settings generally have higher levels of disability and psychological comorbidity than in civilian health care. [21] We have recently shown that procedural treatment effects on disability outcomes in CLBP can be larger in subgroups of people with higher predicted levels of disability, [23] leaving open the possibility that treatment effects in non-VA settings may be smaller than those in the current study. A specific limitation related to activity tracker-evaluated step counts was that post-MBB improvements in step counts were noted for many participants as compared to their pre-MBB steps, and these improvements had not returned to pre-MBB levels for some participants prior to randomization (even though pain intensity levels had returned to an intensity sufficient to warrant LRFA and were ≥4 on the NRS scale on the day of randomization).…”
Section: Discussionmentioning
confidence: 69%
“…Primary life quality instruments are useful to estimate a population's four primary quality of live domains [3,8,9]. The EQ-5D-3L [5] has been utilized to measure life quality for various medical and psychological disorders [10].…”
Section: Introductionmentioning
confidence: 99%
“…18,53 For example, recent studies have used machine learning to promote individualized LSS treatment and to predict the LSS development. 54,55 Second, increasing evidence shows that low physical activity is closely related to LBP, although the causation and dose effects remain uncertain. [56][57][58] Further studies should determine the optimal dosages of physical activity for both populations.…”
mentioning
confidence: 99%